2003
DOI: 10.1038/sj.bjc.6601313
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of classic Kaposi's sarcoma in the Israeli Jewish population between 1960 and 1998

Abstract: Trends in the incidence of classic Kaposi's sarcoma in the Jewish population in Israel for the period between 1960 and 1998 were analysed. World standardised incidence rates of 20.7 and 7.5 per million among men and women, respectively, were calculated. The highest incidence rates were displayed by men originated from Africa and by Asian-born women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
3
20
1
1
Order By: Relevance
“…64 In Israel, rates of classic KS of 2.07 in men and 0.75 in women per 100,000 were calculated. 105 Interestingly, the highest rates were in men of North African lineage, correlating with high levels of antieHHV-8 antibodies. Amazingly, the HHV-8 infection rate among elderly New York City residents showed a seroprevalence of 8.6%, similar among religious groups and not differing by sex or regions of birth.…”
Section: Classic Ksmentioning
confidence: 99%
“…64 In Israel, rates of classic KS of 2.07 in men and 0.75 in women per 100,000 were calculated. 105 Interestingly, the highest rates were in men of North African lineage, correlating with high levels of antieHHV-8 antibodies. Amazingly, the HHV-8 infection rate among elderly New York City residents showed a seroprevalence of 8.6%, similar among religious groups and not differing by sex or regions of birth.…”
Section: Classic Ksmentioning
confidence: 99%
“…The regions with the highest incidence are Africa, where KS represents 3% to 9% of all cancer cases [31], Mediterranean and Eastern European areas, with specific geographic foci in Italy, Greece, and Israel [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…This study found a relatively higher incidence rate among the immigrants from Europe and North America as compared with the general population. However, in Israel, the prevalence of HHV-8 infection [16] and the incidence rate of KS [17] are elevated among immigrants from Morocco and lower among immigrants from North America and Europe. Moreover, IPAH incidence rates in Israel are similar to those reported in the United States and in Europe, while KS incidence rates and HHV-8 prevalence are relatively higher in Israel [18].…”
Section: Discussionmentioning
confidence: 99%